The city as a system : metabolic design for new urban forms & functions - Dooghe, David (2023)
"Difficult problems do not always require far-fetched solutions, but in order to arrive at the solution a change of perspective may be in order. 'The City as a System' advocates such a change of perspective in the study of the urban environment. It posits that designers who wish to truly improve the functioning of the city and solve tricky urban problems cannot afford to only focus on the spatial manifestation of the city, but should also conduct thorough research into the underlying system, into the operation, use, and performance of the urban fabric. The authors view the metabolism of the city as that of a living organism. The urban body--as the place where much of our resource use culminates--plays a crucial role in the transition towards a more sustainable living environment."--Publisher information.
Includes bibliographical references.
Keywords: City planning